2020
DOI: 10.3390/cancers12123573
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Postoperative Radiotherapy for Carcinosarcoma of the Uterus

Abstract: The role of postoperative radiotherapy delivered as external-beam radiotherapy (EBRT), vaginal brachytherapy (VBT) or a combination of both, in the management of carcinosarcoma of the uterus is not clearly defined, as only limited randomized trial data are available, indicating a reduction in locoregional recurrences after EBRT. We performed a structured review of data published from 2010. Although no relevant new data from prospective trials or meta-analyses were identified, 14 analyses of cancer registry dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 24 publications
(27 reference statements)
0
13
0
Order By: Relevance
“…The combination of cisplatin and ifosfamide offers a small improvement in progression-free survival over ifosfamide alone; however, the added toxicity may not justify the use of this combination. 14 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The combination of cisplatin and ifosfamide offers a small improvement in progression-free survival over ifosfamide alone; however, the added toxicity may not justify the use of this combination. 14 …”
Section: Discussionmentioning
confidence: 99%
“…Whereas some studies see the strongest survival effects in patients with positive lymph nodes; propensity-score matched data indicate an overall survival effect of radiotherapy (EBRT + VBT or VBT alone) in FIGO stages I to III, regardless of lymph node surgery. 14 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Radiotherapy, chemotherapy, targeted therapy, and some investigated agents, as well as the combination of any of the above-mentioned therapies (called as multimodality treatment), are believed to provide potentially positive impacts on patients with UCS, and this adjuvant therapy is also apparently beneficial in those with an early UCS. [1][2][3][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] A recent meta-analysis summarizing four studies, which enrolled 2416 patients (939 patients treated with surgery plus postoperative chemotherapy and 1477 patients treated with surgery alone) found that 5-year overall survival (OS) was statistically significantly improved in the combination of surgery and adjuvant chemotherapy group compared to that in the surgery alone group, 23 suggesting that adjuvant chemotherapy should be considered in all UCS patients, regardless of what stages they are. The widely acceptable chemotherapy agents are platinum (either cisplatin or carboplatin), ifosfamide, and paclitaxel.…”
mentioning
confidence: 99%